1985
DOI: 10.1213/00000539-198512000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Does Intravenous Lidocaine Prevent Laryngospasm after Extubation in Children?

Abstract: LElCHT P, WISBORG T, Does intravenous lidocaine prevent laryngospasm after extubation in children? Anesth Analg 1985;64:1193-6. CHRAEMMER-JBRGENSEN B.One huridred otherwise healthy children undergoing tonsillectomy were investigated in a double-blind study to exaiizine the effect of intrazienous lidocaine in preventiiig laryngospasni upon extubation. The children were anesthetized with N,O-0,-halothaize and orally intubated. They were raridonzly given lidocaine, 1.5 mglkg, or saliiie intrazleiiously prior to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
2

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 0 publications
2
48
2
Order By: Relevance
“…However, as the risk of developing hypoxaemia under the clinical condition of 'stridor' (narrowing of the laryngeal aperture) vs 'laryngospasm' (complete closure of the laryngeal aperture) is considerably different, this combined assessment has important limitations. The true incidence of laryngospasm is unknown; Leicht et al [8] could show no effect of intravenous lidocaine on the incidence of laryngospasm; however, they defined laryngospasm as stridor during inspiration, occlusion (no airflow) or the presence of cyanosis. In their study, true laryngospasm, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as the risk of developing hypoxaemia under the clinical condition of 'stridor' (narrowing of the laryngeal aperture) vs 'laryngospasm' (complete closure of the laryngeal aperture) is considerably different, this combined assessment has important limitations. The true incidence of laryngospasm is unknown; Leicht et al [8] could show no effect of intravenous lidocaine on the incidence of laryngospasm; however, they defined laryngospasm as stridor during inspiration, occlusion (no airflow) or the presence of cyanosis. In their study, true laryngospasm, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…An increased incidence of laryngospasm and apnoea is observed in children compared with adults and complications resulting from hypoxaemia are more common and more severe in children [2][3][4]. Lidocaine has been demonstrated to reduce the incidence of laryngospasm in anaesthetised children [5,6]; however, its effectiveness has been questioned [7,8]. Uncertainty regarding its usefulness is partly explained by the fact that most clinical studies were underpowered to assess the relatively rare event of laryngospasm.…”
mentioning
confidence: 99%
“…lidocaine at 2 mg/kg 60-90 s before extubation in children undergoing T&A. However, Leicht et al [99] underwent a similar investigation and found contradictory results; they attributed this to the different time interval of lidocaine administration (4.5 min) and claimed that lidocaine can be effective when trachea is extubated before signs of swallowing occur. Topical lidocaine at 4 mg/kg is equally effective in preventing laryngospasm in children and neonates [54,100].…”
Section: Prevention Using Drugsmentioning
confidence: 99%
“…35 Lidocaine has showed varying effects in this regard, with some studies seeming to show a benefit, 36 and others failing to show this effect. 37 …”
Section: Laryngospasmmentioning
confidence: 99%